The Lion King - Ingoglia, Gina.; Toomey, Marshall; Humphries, Michael (New York : Disney Press, 1994)
The story of Simba, a young African lion cub, who is forced into exile by his evil uncle following the death of his father, the king.
At head of title: Disney's.
Movie version also produced by Disney under same title.
4.5
3-6
3-6
New York Times
Keywords: Lions -- Fiction; Lions -- Fiction; Africa -- Fiction; Africa -- Fiction